A cyclopentasilane–borane compound as a liquid precursor for p-type semiconducting Si. Issue 16 (19th April 2021) - Masuda, Takashi; Nakayama, Maui; Saito, Kimihiko; Katayama, Hirotaka; Terakawa, Akira
Abstract : A liquid precursor for p-type semiconducting Si is synthesized using the dehydrogenative condensation reaction between cyclopentasilane and boron hydride. Abstract : Although little is known about the reaction mechanism between cyclopentasilane (CPS: cyclic Si5 H10 ) and borane (BH3 ), the reaction product is known to be a liquid precursor for p-type semiconducting Si. Therefore, investigation of the reaction mechanism enables more functional material design and contributes to the realization of printable Si semiconductors. Here, we investigated the interaction between CPS and BH3 using density functional theory (DFT) calculations. The calculations showed the occurrence of a dehydrogenative condensation reaction with an energy barrier less than 10 kcal mol −1 . CPS and BH3 act as Lewis bases and acids, respectively, and form somewhat stable reactant complexes with monobridged hydrogen bonds through electrostatic interactions between the positively charged Si atoms and negatively charged B atoms. The monobridged hydrogen bonds initiate dehydrogenation because they abstract other hydrogen atoms in the compound. Eventually, liquid-phase hydrosilanes with Si–B bonds remain as the reaction product. This reaction model and reaction products were also evaluated experimentally using nuclear magnetic resonance spectroscopy, gas chromatography, and gel permeation chromatography. Characterization of the printed Si film also showed that the reaction product can be used as an effective liquid precursor for p-type semiconducting Si.